The Process of Developing a Reading Test: A Review Article - Jahan, Kalsoom; Ashraf, Sharjeel; Mukhtar, Sumaira (International Journal of Psychosocial Rehabilitation, 2020)
This review article discusses the criteria for developing tests for reading skills. Reading skills are input language skills whichare considered as the most basic skills in language learning.The text focuses on the basic approaches used in developing reading tests, selection criteria of texts and authenticity, selection of test items, and the role of Bloom taxonomy in testing reading skills. Asian journal of language testing, Language testing international,Journal of research in reading,Reading research quarterly, Reading for professional purposes, Journal of reading, Journal of reading behaviour, and Language testing are reviewed to answer the research questions.Discussions are analysed and concluded that the level of the learner, objectives, and text itself decide the types of questions that can be constructed and included in reading tests.Different text may tend to different test items such as true-false, multiple-choice, matching, provide information in the table, and yet to add open- ended questions.